Brief Report: Switching From TDF to TAF in HIV/HBV-Coinfected Individuals With Renal Dysfunction—A Prospective Cohort Study. (1st October 2020) - Surial, Bernard; Béguelin, Charles; Chave, Jean-Philippe; Stöckle, Marcel; Boillat-Blanco, Noémie; Doco-Lecompte, Thanh; Bernasconi, Enos; Fehr, Jan; Günthard, Huldrych F.; Schmid, Patrick; Walti, Laura N.; Furrer, Hansjakob; et al.
Abstract : Background: Whereas tenofovir disoproxil fumarate (TDF) can lead to renal adverse events, tenofovir alafenamide (TAF) has a more favorable renal safety profile. However, the impact of replacing TDF with TAF on renal function and liver parameters among HIV/hepatitis B virus (HBV)-coinfected individuals with renal dysfunction remains unclear. Methods: We included all participants from the Swiss HIV Cohort Study with an HIV/HBV coinfection who switched from TDF to TAF and had an estimated glomerular filtration rate (eGFR) <90 mL/min/1.73 m 2 and a suppressed HIV viral load (<200 cp/mL). We assessed changes in eGFR, urine protein-to-creatinine ratio, and alanine aminotransferase (ALT) after 1 year using mixed-effect models with interrupted time series. Results: Among 106 participants (15.1% women, median age 53 years), eGFR was 60–89 mL/min/1.73 m 2 in 84 (79.2%) and <60 mL/min/1.73 m 2 in 22 (20.8%) individuals at the time of switch. One year after the switch from TDF to TAF, individuals with an eGFR between 60 and 89 mL/min/1.73 m 2 experienced increases in eGFR of 3.2 mL/min/1.73 m 2 (95% confidence interval [CI] 1.2 to 5.2), whereas those with an eGFR <60 mL/min/1.73 m 2 experienced improvements of 6.2 mL/min/1.73 m 2 (95% CI 2.4 to 10.0). Urine protein-to-creatinine ratio decreased overall (−6.3 mg/mmol, 95% CI −10.0 to −2.7), and ALT levels declined in patients with elevated baseline levels (−11.8 IU/L, 95% CI −17.3 to −6.4) 1 year after replacing TDF with TAF. Conclusions: Switching from TDF to TAF among HIV/HBV-coinfected individuals with renal impairment led to improvements in eGFR, a decline in proteinuria, and to ALT normalization in those with elevated ALT levels. Abstract : Supplemental Digital Content is Available in the Text.